Digital Transformation and the Application of Artificial Intelligence in the Financial Sector - Kosh Jr, Emory; Rohim, Ahmad Miftahur (Jurnal Perbankan Syariah, 2025)
Abstract: The digital transformation driven by advances in Artificial Intelligence (AI) has fundamentally changed the way the financial sector operates. This study aims to analyze the application of AI and digital technologies in the financial industry, including banking, fintech, and insurtech, as well as to identify the benefits, challenges, and future prospects. Using a qualitative approach based on literature review, the findings reveal that AI significantly contributes to operational efficiency, service personalization, and the expansion of financial inclusion. The implementation of technologies such as machine learning, NLP-based chatbots, robo-advisory platforms, and user data processing in insurance has enhanced the speed, accuracy, and reach of financial services. Nevertheless, major challenges remain, particularly in terms of data privacy protection, algorithmic bias, and cybersecurity. This study recommends strengthening regulations and developing adaptive security systems to ensure that financial digitalization proceeds in a safe, fair, and sustainable manner.